Investigation of Rheological Test Methods for the Suitability of Mortars for Manufacturing of Textile-Reinforced Concrete Using a Laboratory Mortar Extruder (LabMorTex) - Matthias Kalthoff; Michael Raupach; Thomas Matschei (Construction Materials, 2022)
One of the promising technologies to produce carbon textile-reinforced concrete structures is extrusion. For defect-free extrusion, high requirements are placed on the fresh concrete, since it must be transportable through the augers in the extruder and must not change the desired geometric shape after leaving the mouthpiece. For the rheologic description of suitable concretes or mortars for the extrusion process, there is currently a lack of test methods to characterise the fresh concrete before extrusion. At present, new mixtures are first tested in elaborate trials on laboratory extruders before they can be transferred to production scale. The development of compounds is strongly dependent on the know-how and experience of the users. Within the scope of this paper, different methods were investigated and systematic suitability tests for a successful extrusion have been carried out. The results show that the fresh mortar can only be roughly described by the measured data during the mixing process, such as the temperature or the torque. The use of a capillary rheometer only allows a basic characterisation of the fresh mortar. A clear differentiation of the fresh mortar can be made with the help of sphere penetration tests. These allow the mortar to be classified as unsuitable for the extrusion process or as extrudable before the extrusion process, and the suitability of new mixtures can be assessed in advance. The newly developed method offers the possibility of greatly accelerating the implementation of new formulations for the extrusion process, regardless of the experience of the subsequent users, and reducing the need for complex experiments using laboratory extruders.